Readiness for Artificial Intelligence Integration in Government Services: Perspectives from Ramechhap District Employees - Mahat, Dipak (Jurnal Multidisiplin Madani, 2024)
The study aimed to investigate the perception of government services employees regarding the future perspective of AI in government services and to compare the perspectives between federal and local level employees. Research adopted objectivity methods to explore the result. Data collected from federal and local government employees in Ramechhap District, Bagmati Province of Nepal. The study revealed insights into the perception of government services employees regarding AI in government services, indicating a moderate belief in AI's potential to enhance job efficiency and a cautious optimism towards AI integration within organizations. Respondents recognized the importance of investing in AI infrastructure and training, foreseeing changes in daily tasks and increased AI usage in service tasks. Anticipation of new HR roles and a demand for flexible virtual work setups was also noted. The ANOVA results comparing federal and local level employees' perspectives on AI in government services showed no significant difference between the two groups, suggesting that the variation in perspectives was not statistically significant. This research provides valuable insights into the perceptions and expectations of government services employees regarding AI adoption and its potential impact on future work environments